A Contrastive Analysis Of Interrogative Sentences In English and Indonesian - Ruth Monika Simanjuntak; Nadya Bersista E Marbun; Mutiara Rajagukguk; Anita Sitanggang (Jurnal Ilmu Pendidikan dan Sosial, 2023)
The purpose of this article was to provide an overview of the survey Structures in Indonesian and English to explore similarities and Differences between them and make some predictions based on them These similarities and differences. This research uses descriptive qualitative research. In this study, data analysis was used according to Miles and Huberman using three methods for data analysis, namely data reduction, data visualization, and drawing conclusions. The purpose of this study is to find out "A Contrastive Analysis of Interrogative Sentences in English and Indonesia". The comparison of two languages in terms of asking questions leads to the following conclusions regarding the above-mentioned similarities and differences: given that there are questions in Indonesian and English have many characteristics, allowing Indonesian English learners to simply formulate the inquiry in the target language.